HBV- and HCV-Related Infections and Risk of Pancreatic Cancer - Fiorino, Sirio; Cuppini, Andrea; Castellani, Gastone; Bacchi-Reggiani, Maria Letizia; Jovine, Elio (JOP. Journal of the Pancreas, 2013)
Pancreatic carcinoma is one of the most lethal cancers in humans. The poor prognosis of this malignancy depends on several factors, such as: lack of early symptoms, advanced stage at detection, early metastatic spread and no effective systemic treatment. To date, only few risk factors for this malignancy are known; therefore, considerable efforts are required to identify additional causative agents involved in the process of pancreatic carcinogenesis. In the last years, a large series of epidemiological investigations have suggested that both bacteria and viruses may play a important role in the initiation and progression of several animal and human cancers. In particular, some studies have showed that hepatitis B (HBV) and hepatitis C (HCV) viruses, two hepatotropic pathogens with well-known oncogenic properties for liver, may be detected also in extra-hepatic tissues, such as pancreas. The aim of this paper is to briefly report the results of available studies, assessing the possible association between HBV/HCV and pancreatic cancer development as well as to discuss the limiting factors of these researches. Image: Hepatitis C virus.